Eco-Engineered Bioreactors : Advanced Natural Wastewater Treatment - Higgins, James; Mattes, Al.; Stiebel, William; Wootton, Brent (London : Taylor and Francis, 2017)
"This book provides a detailed understanding of a new, highly innovative natural wastewater treatment method called Engineered Bioreactors (EBs), which have been shown to provide superior removal methods for many kinds of pollutants and contaminants. Treatment using EBs involves passing wastewater through excavated basins (cells) in which microbes are introduced using fixed films on permeable substrate media. The book traces the development of the biological and ecological Engineered Bioreactor technology and presents information on the types, morphologies, testing methods for, designs, microbiology, and operations of EBs of all kinds."--Provided by publisher.
Chapter 1 Introduction -- chapter 2 Wastewaters Treatable in EEBs -- chapter 3 Aerobic Eco-Engineered Bioreactor Ecotechnologies -- chapter 4 Anaerobic Eco-Engineered Bioreactors -- chapter 5 Biochemical Reactors -- chapter 6 Treatability Testing -- chapter 7 Eco-Engineered Bioreactor Substrates -- chapter 8 The Design of EEB Systems -- chapter 9 Summary and State-of-the-Art.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING -- Civil -- Soil & Rock; TECHNOLOGY & ENGINEERING -- Environmental -- Water Supply